A Beef Value Chain Strategy for Minimizing Logistic Cost in Tasikmalaya, West Java - Evan Nugraha; Rini Mulyani Sari; Asep Kurniawan (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
Indonesia's economy, cattle farming industry and beef pricing have failed to satisfy the community's requirements. Because of the low productivity of beef cattle, the government is forced to import beef to fulfil customer demand, one of which is imported frozen from Australia. Because of the scarcity of local beef, the average price of local beef is $8.32 per kilogram, which is more than imported beef, and local beef demand is much greater. Many people with a lower middle income find it challenging to consume beef because of the current price situation. As a result of this occurrence, research must be conducted using a value chain analysis technique to determine the source of the high price of local beef. The findings of this study potentially resulted in a 35% drop in consumer selling value from the current pricing.